Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Smartphone Iphone di Banjarmasin - Norbaiti Norbaiti; Winda Setia Rahmi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
This study aims to determine the effect of product quality and brand image on purchasing decisions of iphone smartphones in Banjarmasin both simultaneously and partially. The population of this research is the people in Banjarmasin, while the samples taken are 100 respondents using purposive sampling technique. This study uses a quantitative approach. The research instrument was tested for validity and reliability by looking at corrected items total correlation and Cronbach's alpha and all were declared valid and reliable. Data analysis techniques used in this study used the classic assumption test, multiple linear regression analysis, and hypothesis testing (F test and t test). The results of this study indicate simultaneously that product quality and brand image have a positive effect on purchasing decisions for iPhone smartphones and the most dominant factor influencing purchase decisions is on the brand image. Partially for product quality has a positive effect on purchasing decisions with a t value greater than t table that is 4.674> 1.964 with a significance value of 0.000. As for the brand image, it also has a positive influence on purchasing decisions with a t value greater than t table, namely 20.554> 1.964 with a significance value of 0.000.